Vernizes fluoretados: uma revisão de literatura sobre aplicação clínica - Souza, Bruno Victor da Silva (2022)
The use of fluoride emerged decades ago in clinical dental practice. Among the formulations for professional use and with wide clinical application, dental varnishes stand out due to their great adhesion to the dental wall and the slow and gradual release of the active ingredients, thus extending the effect of the therapeutic agent delivered. The present study sought to carry out a review of the literature on the use of fluoride dental varnishes, pointing out the main current evidence and indications about these formulations. For this, a literature review was carried out with the descriptors dental varnishes, fluorides and dental caries, using the PUBMED and BVS databases. In the end, a total of 24 references were used for data extraction. At the public health level, varnishes are considered a safe, effective and efficient oral health promotion strategy to reduce dental caries in vulnerable populations. In addition, it has strong indication for children and special patients. Currently, there are more than thirty fluoride varnishes on the market, with different applied systems and variable pharmacokinetics, however their composition coincides with most brands. It is concluded that dental varnishes, even after decades of their emergence, still have strong application in Dentistry, especially those whose active principle is fluoride. Its use is recommended especially in children, special patients and patients undergoing orthodontic treatment, for the prevention and control of dental caries.